Characteristics of Improvement of Improvement Techniques in Brazilian Grape Production - Ana Lúcia de Oliveira Borges; Tais Karinna de Oliveira Borges; Aline Rocha (Boletim de Indústria Animal, 2022)
Agricultural activities in Brazil have steadily increased in recent years, due to all the advantages that the country has, from natural resources to the expectation of production and consumption of investors and society in general. The Northeast region, specifically the São Francisco Valley region (municipalities of Casa Nova, Curaçá and Juazeiro, Bahia, and Petrolina, Pernambuco) is considered apt for grape production. According to the observed data, from 2008 to 2015, the entry of international certifiers, together with the work of the Brazilian Agricultural Research Corporation (EMBRAPA), generated improved results for the production of wine and table grapes, marketed both in the country and abroad. In the 1990s, for example, farms produced few varieties, and lost more than 40% of production to infestations of pests and pathogens and natural phenomena. Currently, farmers can use technologies, business plans, partnerships with research institutes such as International Fruit Genetics (IFG) and other companies that sell certified seedlings and evaluate crops with the necessary characteristics for the nomenclature of the product to maintain the standards accepted worldwide. Thanks to the results of adaptation, genetics, vigor, post-harvest quality and crispness, Brazilian grapes are recognized as tasty, resistant and available throughout the year. International trade includes varieties such as Scarlota, Arra 15, Arra 32, Saphiro, Jubilee, Victoria, Thompson and many others. New ventures involving grapes in recent years have been increasing the types of fruit. In some farms, more than 20 varieties are produced, of which 2, developed with EMBRAPA, have national dominance, in contrast to more than 50 types coming from Europe and North America to serve the global market. Other fruits such as lemons, oranges, avocados and apples, among others, are being tested for export markets, but the grape business in Brazil stands out for expansion based on technology, innovation and a strong market. The search for innovative propagation materials accepted by modern consumers has favored the production of genetically improved cultivars, enabling the maintenance of modern and efficient agriculture.